High active pd@mil-101 catalyst for dehydrogenation of liquid organic hydrogen carrier. (11th June 2020) - Ding, Chenghan; Zhu, Ting; Wang, Fanyi; Zhang, Zhiming; Dong, Yuan; Yang, Ming; Cheng, Guoe; Ke, Hanzhong; Cheng, Hansong
Abstract: Highly dispersed Pd nanoparticles immobilized in MIL-101 (Pd@MIL-101) were prepared and used for the catalytic dehydrogenation of Liquid organic hydrogen carriers (LOHC). The as-synthesized catalysts were characterized and it was found that 3 wt% of Pd@MIL-101 embodied smaller and highly dispersed Pd NPs. The catalytic activities of as-synthesized catalysts were investigated by the dehydrogenation of a representative LOHC compound, perhydro-N-propylcarbazole (12H-NPCZ). The results indicated that 3 wt% Pd@MIL-101 catalyst exhibited good catalytic activity and good reusability for the dehydrogenation of 12H-NPCZ, which is superior to that of commercial 5 wt% Pd/Al2 O3 catalyst. This study demonstrates that Pd@MIL-101 is a promising dehydrogenation catalyst for the application of LOHC technology. Graphical abstract: Image 1 Highlights: Highly dispersed Pd NPs immobilized in MIL-101 (Pd@MIL-101) were prepared. 3 wt% catalyst exhibits better catalytic activity than commercial 5 wt% Pd/Al2 O3. Pd@MIL-101 shows good reusability for the catalytic dehydrogenation of 12H-NPCZ.